2022
DOI: 10.3390/ijerph19020897
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Knowledge, Prevention, and Occurrence of Sexually Transmitted Infections among Freshmen from Four Italian Universities

Abstract: Background. The peak of sexually transmitted infections (STI) among adolescents/young adults suggests a low level of prevention. In order to assess whether the level of sexual health education (SHE), received by several channels, was effective at improving sexual behaviors, we conducted a survey among freshmen from four Italian universities. Methods. This observational cross-sectional study was conducted with an anonymous self-reported paper questionnaire, administered during teaching lectures to university fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
5
17
1
Order By: Relevance
“…However, our study revealed that women who had prior knowledge of gonorrhea, syphilis, and HIV had a twofold higher risk of testing positive for an STI. Higher associations between a higher risk of STIs and STI knowledge were also reported by others [ 32 , 33 , 34 , 35 , 36 ]. Interestingly, women who had prior knowledge of chlamydia were 51% less likely to test positive for STIs compared to women who were not aware of chlamydia.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, our study revealed that women who had prior knowledge of gonorrhea, syphilis, and HIV had a twofold higher risk of testing positive for an STI. Higher associations between a higher risk of STIs and STI knowledge were also reported by others [ 32 , 33 , 34 , 35 , 36 ]. Interestingly, women who had prior knowledge of chlamydia were 51% less likely to test positive for STIs compared to women who were not aware of chlamydia.…”
Section: Discussionsupporting
confidence: 77%
“…This might be the reason for the unexpected result of higher STIs among the study participants who had more knowledge of STIs. As others have reported, knowledge about STIs was most likely acquired from direct experience than from learning how to prevent infection [ 32 ]. Nzoputam et al reported that respondents with a good knowledge of STIs had a greater tendency to test positive for STIs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, students in a higher year of study and those from medical faculties achieved a higher STI quiz score. This finding was similar to that reported in a study among students from four Italian universities ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the Italian study (19), the overall STI knowledge among our students, regardless of the type of secondary school attended, was unsatisfactory. The average quiz score of This table shows the comparisons of characteristics between students from international schools and those from local schools.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation